Verstaatlichung in Krisenzeiten - Politik und Ökonomie - Brangsch, Lutz (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2009)
During the last years it was otten maintained that the state is dead, However, in the course of the economic crisis the state has turned out capable of acting. State interventions play with the fight of the crisis a central role. Steps to the nationalisation of enterprise cause special interest, The article examines, which interests stand behind this type of state intervention, who is in this case really the state and which consequences arise for left movements, Nationalisation is described as a contradictory process whose results depend highly on the legal capacity of left movements.